Development of poly ADP-ribose polymerase-1 inhibitor with anti-cervical carcinoma activity - Zhang, Tong-Mei; Wang, Wen (Cellular and Molecular Biology, 2020)
This research aimed to discover and identify new poly ADP-ribose polymerase-1 (PARP) inhibitors with potent anti-cervical carcinoma activity, and then explore their potential biological roles on cervical carcinoma cell. For this purpose, we identified a new PARP inhibitor from a high-throughput virtual screening method and found that the compound strongly inhibited cervical carcinoma HeLa cell. Cell proliferation was evaluated by an MTT assay, and the cell apoptosis was assessed by flow cytometry. Results showed that PARP1 is a poly ADP-ribose catalyzing enzyme in eukaryotic cells, which is activated during DNA damage and repair, and plays an important role in DNA repair and cell apoptosis. Herein we report the first discovery of a new PARP inhibitor from a high-throughput virtual screening method, then the compound was measured its anti-cervical carcinoma activity by using an MTT assay, which suggested that the compound strongly inhibited HeLa cell proliferation, the IC50 value is 0.65 µM. In addition, the compound induced HeLa cell apoptosis in a dose-response manner. All these data suggested that the compound is a promising lead compound, which deserves further investigation. It is concluded that the compound discover herein is a promising PARP-1 inhibitor with potent anti-cervical carcinoma activity, which deserves further investigation.